Analysis of Expense Recording Reports in MSMEs in the Pangkalan Mahsyur Subdistrict - Ihsan, Khairil; Nurlaila, Nurlaila (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Micro, Small, and Medium Enterprises (MSMEs) are essential to Indonesia’s economy, contributing over 60% to the national GDP and employing approximately 97% of the workforce. Despite their significance, many MSMEs struggle with effective financial management, particularly in terms of expense and cost reporting. Common challenges include a lack of accounting knowledge and limited access to technology, which impact the accuracy and efficiency of financial documentation.This study explores expense recording practices among MSMEs in the Pangkalan Mahsyur District, aiming to identify practical solutions to improve financial recording. Accurate expense documentation provides significant benefits for MSMEs, including better cost control, performance assessment, tax compliance, and the potential to attract investors or access financial loans. These advantages collectively contribute to the sustainable growth and resilience of MSMEs, allowing them to compete more effectively in the market.To overcome these record-keeping challenges, MSMEs can gain from ongoing education and training focused on basic accounting principles. This approach can be complemented by adopting accounting software or consulting services that cater specifically to their needs. By increasing financial literacy and leveraging relevant technologies, MSMEs can enhance their financial management practices, creating a foundation for improved operational efficiency, strategic planning, and future growth opportunities. Through these efforts, MSMEs can build a more robust financial infrastructure, ensuring they continue to thrive in Indonesia’s dynamic economy.